2019
DOI: 10.1038/s41366-019-0399-8
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic evidence that hypothalamic gliosis is improved after bariatric surgery in obese women with type 2 diabetes

Abstract: Background/Objectives-Hypothalamic neurons play a major role in the control of body mass. Obese subjects present radiologic signs of gliosis in the hypothalamus, which may reflect the damage or loss of neurons involved in whole-body energy homeostasis. It is currently unknown if hypothalamic gliosis (1) differs between obese nondiabetic (ND) and obese diabetic subjects (T2D) or (2) is modified by extensive body mass reduction via Roux-n-Y gastric bypass (RYGB). Subjects/Methods-Fifty-five subjects (all female)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…34 However, inflammation in the brain does not replicate the usual process seen in the periphery with the recruitment of peripheral immune cells. This is largely a result of the presence of The hypothalamic signal significantly correlated positively with BMI, 8 the magnitude of peripheral insulin resistance 41,42 and systemic lowgrade inflammation. 43 Importantly, MRI postmortem scans and histological staining confirmed that the signal detected by in vivo MRI is a valid surrogate measure for hypothalamic inflammation.…”
Section: No Significant Association Between Baseline Cerebral Bloodmentioning
confidence: 99%
See 1 more Smart Citation
“…34 However, inflammation in the brain does not replicate the usual process seen in the periphery with the recruitment of peripheral immune cells. This is largely a result of the presence of The hypothalamic signal significantly correlated positively with BMI, 8 the magnitude of peripheral insulin resistance 41,42 and systemic lowgrade inflammation. 43 Importantly, MRI postmortem scans and histological staining confirmed that the signal detected by in vivo MRI is a valid surrogate measure for hypothalamic inflammation.…”
Section: No Significant Association Between Baseline Cerebral Bloodmentioning
confidence: 99%
“…Whether brain inflammation is reversible is currently not known. The initial evidence suggests that some aspects of neuroinflammation can be rescued in both humans and rodents 35,42. However, it is not known whether this is the result of direct central effects or is caused by decreased peripheral inflammation.…”
mentioning
confidence: 99%
“…It is worth noting that the vascular and inflammatory effects of obesity may play a role in the development of neurodegenerative diseases such as AD ( Naderali et al, 2009 ; Businaro et al, 2012 ; Walker and Harrison, 2015 ). Relatedly, obese women presented a decrease in BBB function ( Gustafson et al, 2007 ) while bariatric surgery reversed obesity and reduced hypothalamic gliosis in women ( van de Sande-Lee et al, 2020 ).…”
Section: Metabolic Diseases As a Risk Factor For Neurodegenerative DImentioning
confidence: 99%
“…Using quantitative structural neuroimaging techniques, several studies have found radiologic evidence of gliosis of the MBH in association with obesity in adults (103,113,114) and children (115). Moreover, longer MBH T2 relaxation times correlate with greater visceral adiposity (115,116) and insulin resistance independent of obesity (113) and were observed in women with obesity with type 2 diabetes mellitus relative to women with obesity who were nondiabetic (102).…”
Section: Structural Neuroimagingmentioning
confidence: 99%